The impact of antistigma education on the attitudes of general practitioners regarding schizophrenia - (:unkn) unknown (BLACKWELL PUBLISHING, 2006)
The aim of this study was to examine the views and attitudes of general practitioners (GP) with respect to schizophrenia, and the changes in their attitudes after antistigma education. A total of 106 GPs working in 71 health institutions were included in the study. A questionnaire of 16 items, focussing on doctors' views and attitudes towards schizophrenia, was applied. Questions were about the views and attitudes of doctors towards general myths related to schizophrenia. Doctors were asked to select one of two responses: 'I agree' or 'I disagree', for statements such as 'schizophrenic patients cannot work' and 'schizophrenic patients are aggressive and dangerous'. After completing the questionnaire, all the GPs were given a single session of antistigma education. The questionnaire was repeated 3 months after training meetings in a subsample of 54 GPs which represented the whole sample in terms of gender, age, and years in medical practice. The authors found statistically significant, positive changes on five items out of the 16 items in the post-test survey when compared to attitudes before training, including items about the treatability of schizophrenia, harmfulness and untrustworthiness of schizophrenic patients. The authors' findings suggest that one antistigma education session, supported by the distribution of related documents, can improve GPs attitudes towards schizophrenia.
Keywords: general practitioners; schizophrenia; stigma; MENTAL-ILLNESS; COMMUNITY ATTITUDES; PSYCHIATRIC-CARE; PEOPLE; STIGMA; PROFESSIONALS; DANGEROUSNESS